Watch arranged on hat - CHEN DONGNI (2013)
Provided is a watch arranged on a hat. The watch arranged on the hat is characterized in that the hat (1) is provided, and two snap fastener bottoms (2) are arranged on the hat (1); a watch band (4) of the watch (3) is equipped with two snap fastener covers (5) that correspond to the snap fastener bottoms (2); and the snap fastener covers (5) are disposed on the snap fastener bottoms (2). The watch arranged on the hat exhibits a decorative effect, enables a user to conveniently check time on the watch, helps the user to relieve burden for wearing the watch on a wrist, and is in favor of health of the user.